2010
DOI: 10.1111/j.1439-0329.2010.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Diplodia pinea endophytic infections in Pinus patula and P. radiata seedlings in South Africa

Abstract: Diplodia pinea, an opportunistic and latent pathogen, can significantly affect Pinus productivity worldwide. Despite being studied in South Africa for almost 100 years, the source of D. pinea inoculum responsible for seedling infection is unknown. The aim of this study was to determine the role of seed in vertical transmission of D. pinea and to investigate sources of inoculum leading to horizontal transmission to pine seedlings. Surface-disinfected seeds were inoculated with spore and mycelium suspensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
0
41
0
2
Order By: Relevance
“…Many members have a broad host range (Punithalingam 1976(Punithalingam , 1980, they fruit on senescing tissue , are found in above ground plant parts (Johnson et al 1992) and multiple species are found often within localised infections in the host tissue (Sakalidis et al 2011a, b;Spagnolo et al 2011). However; unlike other Class III fungi they have occasionally been observed in host seeds (Johnson et al 1998;Bihon et al 2011) and there is also evidence of infections in horticultural crops occurring via pruning wounds (Brown and Hendrix 1981;Smith et al 1994Smith et al , 1996Amponsah et al 2011;Sakalidis et al 2011c). Pathogenicity trials are successfully used to prove potential for disease development (Amponsah et al 2011;Sakalidis et al 2011c) but little is known about possible passive (endophytic) or delayed active (latent pathogen) life stages that may also initiate from the same infections.…”
Section: Introductionmentioning
confidence: 99%
“…Many members have a broad host range (Punithalingam 1976(Punithalingam , 1980, they fruit on senescing tissue , are found in above ground plant parts (Johnson et al 1992) and multiple species are found often within localised infections in the host tissue (Sakalidis et al 2011a, b;Spagnolo et al 2011). However; unlike other Class III fungi they have occasionally been observed in host seeds (Johnson et al 1998;Bihon et al 2011) and there is also evidence of infections in horticultural crops occurring via pruning wounds (Brown and Hendrix 1981;Smith et al 1994Smith et al , 1996Amponsah et al 2011;Sakalidis et al 2011c). Pathogenicity trials are successfully used to prove potential for disease development (Amponsah et al 2011;Sakalidis et al 2011c) but little is known about possible passive (endophytic) or delayed active (latent pathogen) life stages that may also initiate from the same infections.…”
Section: Introductionmentioning
confidence: 99%
“…Although he found that while D. pinea was present in all samples of several consignments of imported ponderosa pine seeds, the frequency of 'infected seed' determined after surface disinfestation never exceeded 0.2%. In South Africa, Bihon et al (2011a) isolated D. pinea from 2.3% of Monterey pine seeds, and 0% of Mexican weeping pine seeds that were first surface-disinfested. Fraedrich et al (1994) studied factors affecting frequency of fungi cultured from seeds of slash pines in a seed orchard in Florida.…”
Section: Resultsmentioning
confidence: 99%
“…& Cham.) (Smith et al 1996(Smith et al , 2002, Monterey pine (P. radiata) (Smith et al 1996;Bihon et al 2011a) and slash pine (P. elliottii Englem.) (Anderson et al 1984;Huang & Kuhlman 1990;Fraedrich et al 1994;Fraedrich & Miller 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the potential of D. pinea to be distributed via seed is very low (Bihon et al 2010) and the fungus is not insectvectored. Limited long distance dispersal, geographical barriers and reproductive isolation between populations should, therefore, lead to isolated populations that are differentiated from each other.…”
Section: Discussionmentioning
confidence: 98%
“…are grown (Swart and Wingfield 1991;Stanosz et al 1999;Burgess et al 2001a;Feci et al 2003). Diplodia pinea is thought to have been moved around the world with pine planting stock most probably in its endophytic form as well as with seeds or seed lots contaminated with debris (Wingfield et al 2001;Burgess and Wingfield 2002;Bihon et al 2010). The introduced populations of D. pinea have been characterized in only a few instances (Smith et al 2000;Burgess et al 2001aBurgess et al , b, 2004.…”
Section: Introductionmentioning
confidence: 96%